2020
DOI: 10.1111/ijfs.14511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyphenol from apple peel extract on the survival of probiotics in yoghurt ice cream

Abstract: The objective of this study was to evaluate the effect of apple peel polyphenol extract (APPE) on the microbiological and physicochemical properties of yoghurt ice cream stored at À20°C for 90 days. Five level of APPE were added in yoghurt ice cream as: CTL (control without APPE); AE1 (1% APPE); AE2 (2% APPE); AE3 (3% APPE); AE4 (4% APPE); and AE5 (5% APPE). Samples with APPE had viable counts of Lactobacillus acidophilus and Bifidobacterium lactis of ≥8 log cfu g À1 and >7 log cfu g À1 , respectively, during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
16
3
Order By: Relevance
“…It should also be noted that plant-derived substances can become an additional nutrient for probiotic microorganisms while providing a protective substance against the adverse effects of the external environment. Ahmad et al [ 61 ] obtained promising results using polyphenols extracted from apples to protect the Bifidobacterium lactis bacteria during freezing. In the light of these studies, we can see the great potential of our obtained emulsions to stimulate growth and protect probiotic bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…It should also be noted that plant-derived substances can become an additional nutrient for probiotic microorganisms while providing a protective substance against the adverse effects of the external environment. Ahmad et al [ 61 ] obtained promising results using polyphenols extracted from apples to protect the Bifidobacterium lactis bacteria during freezing. In the light of these studies, we can see the great potential of our obtained emulsions to stimulate growth and protect probiotic bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Ahmad et al. (2020) also claimed that adding apple peel polyphenol extract with appropriate concentration to yoghurt ice cream positively affected the probiotic bacterial survival. According to the results, it can be concluded that honey had a predominant effect on the probiotic strain of this study ( L. acidophilus LA‐5).…”
Section: Resultsmentioning
confidence: 99%
“…The overrun rate was detected by weighing the same volume of ice cream after and before freezing in the same volumetric cylinder (Ahmad et al, 2020).…”
Section: Analyses Of Ice Cream MIXmentioning
confidence: 99%